A case study on the changes in the textiles and textile industries of Bontoc and Sagada - Aliasas, Anne Nicole Alyssandra V.
The main objective of the case study was to identify the changes in the textiles and textile industries of Bontoc and Sagada by comparing their pre-commoditized textiles and commoditized textiles. The changes were analyzed using Hall's (2004) concepts of change: traditionalism, innovation (simplification, hybridization, color experimentation) and imitation. This study also aimed to identify the cultural and economic changes in the textile industries of the communities. This was done through interviews and physical observation. The commoditized textiles were compared with pre-commoditized textiles as described in the literature. The researcher found the concepts of change (Hall, 2004) were observed in the commoditized textiles. The commoditized textiles have more vibrant color combinations than the pre-commoditized textiles due to market demand and availability of threads. Pre-commoditized symbols are also modified to adapt to commoditized textiles. It was also found that the symbols that are present in the textiles of both communities have no meaning for both the maker and the user. The products produced from fabrics are no longer confined to pre-commoditized items, but is now targeted towards the external market. Although there is general economic progress in the area, the cultural sustainability may need more attention. The practice of producing textiles through pre-commoditized weaving methods is preserved in both communities. The researcher believes that the cultural value can still be preserved if the community will either re-learn the cultural and symbolic meanings and values that are attached to their textiles, and/or create a new set of cultural and symbolic meanings and values to attach to the commoditized textiles that they are now developing. A School of Living Traditions could be established in their educational system to sustain their culture.